Assessment of upper tropospheric and stratospheric water vapor and ozone in reanalyses as part of S-RIP - Davies, S. M.; Hegglin, M. I.; Fujiwara, M.; Dragani, R.; Harada, Y.; Kobayashi, C.; Long, C. L.; Manney, G. L.; Nash, E. R.; Potter, G. L.; Tegtmeier, S.; Wang, T.; et al. (Atmospheric Chemistry and Physics, 2017)
Reanalysis data sets are widely used to understand atmospheric processes and past variability, and are often used to stand in as “observations” for comparisons with climate model output. Because of the central role of water vapor (WV) and ozone (O3) in climate change, it is important to understand how accurately and consistently these species are represented in existing global reanalyses. In this paper, we present the results of WV and O3 intercomparisons that have been performed as part of the SPARC (Stratosphere–troposphere Processes and their Role in Climate) Reanalysis Intercomparison Project (S-RIP). The comparisons cover a range of timescales and evaluate both inter-reanalysis and observation-reanalysis differences. We also provide a systematic documentation of the treatment of WV and O3 in current reanalyses to aid future research and guide the interpretation of differences amongst reanalysis fields. The assimilation of total column ozone (TCO) observations in newer reanalyses results in realistic representations of TCO in reanalyses except when data coverage is lacking, such as during polar night. The vertical distribution of ozone is also relatively well represented in the stratosphere in reanalyses, particularly given the relatively weak constraints on ozone vertical structure provided by most assimilated observations and the simplistic representations of ozone photochemical processes in most of the reanalysis forecast models. However, significant biases in the vertical distribution of ozone are found in the upper troposphere and lower stratosphere in all reanalyses.